Unraveling cooperative interactions between complexed ions in dual-host strategy for cesium salt separation - Liu, Zhihua; Chen, Ya-Zhi; Wang, Ji; Nie, Qingling; Zhao, Wei; Wu, Biao (Beilstein Journal of Organic Chemistry, 2025)
The dual-host strategy offers a straightforward approach to ion separation, yet the nature of cooperative interactions between receptor-complexed cations and anions remains poorly understood. In this study, we utilize 18-crown-6 as a cation receptor and a tripodal hexaurea receptor L as an anion receptor to extract cesium salts (chloride, nitrate, carbonate, sulfate, and phosphate) from the solid phase into chloroform. Remarkably, Cs3PO4 exhibits the highest extraction efficiency, driven by strong cooperative interactions involving ion-dipole coordination between Cs+ and carbonyl (C=O) groups, as well as direct ion-pairing interactions between 18-crown-6-complexed Cs+ and hexaurea-bound PO43−. Single-crystal structural analysis corroborates these interactions, shedding light on the underlying mechanisms and providing valuable guidance for the rational design of advanced dual-host systems for selective ion separation.
Keywords: anion binding; cesium extraction; dual-host strategy; ion-pair interaction; solid–liquid extraction